2006
DOI: 10.1159/000097110
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Fetal Intracardiac Transfusion for Thrombocytopenia and Acute Hypovolemia due to Cordocentesis-Associated Hemorrhage in Parvovirus-Induced Hydrops

Abstract: Objectives: To demonstrate the utility of fetal intracardiac transfusion to correct acute fetal hypovolemia and thrombocytopenia in fetal Parvovirus infection. Methods: Intracardiac transfusion in a 19-week gestation was indicated due to cordocentesis-associated hemorrhage. Results: Intracardiac transfusion resulted in correction of acute bradycardia, anemia and thrombocytopenia and persistent umbilical cord hemorrhage following attempted intravascular transfusion. Conclusions: This case illustrates the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[15][16][17] In adults, the use of EUS plays a major role in the diagnosis and management of gastroenterologic and oncologic disorders. In addition to staging GI and pancreaticobiliary malignancies, EUS guidance has been used to perform various less-invasive but effective therapeutic interventions such as celiac nerve block and pancreatic pseudocyst drainage.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In adults, the use of EUS plays a major role in the diagnosis and management of gastroenterologic and oncologic disorders. In addition to staging GI and pancreaticobiliary malignancies, EUS guidance has been used to perform various less-invasive but effective therapeutic interventions such as celiac nerve block and pancreatic pseudocyst drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies including complete blood count [13,14] , platelet count [21] , Kleihauer-Betke analysis (for documentation of a pure sample of fetal blood), metabolic profile, serologies for transplacental viral/protozoal infection, direct Coombs' assays and fetal blood gas analysis [22] may be reliably obtained and interpreted. Antsaklis et al [12] reported 158 cases of fetal cardiocentesis during the second trimester for the prenatal diagnosis of fetal hemoglobinopathy.…”
Section: Diagnostic Cardiocentesismentioning
confidence: 99%
“…Though some data suggest that up to one-third of fetuses will experience spontaneous resolution [24] , intrauterine intravascular transfusion is felt to be the treatment of choice [25] , providing the best overall outcome. Sarno et al [21] reported successful reversal of hydrops due to fetal parvovirus infection in a 19-week gestation by a single intracardiac transfusion in a procedure complicated by hemorrhage from the initial attempt at cordocentesis.…”
Section: Parvovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…These anatomic characteristics make the fetal right ventricle the most anterior cardiac chamber and the closest to the anterior chest wall, providing the shortest path to the fetal heart (Figure 2). 6 After insertion of a 22‐gauge needle into the amniotic cavity, the anterior chest wall should be approached perpendicularly. The right ventricle should be entered carefully through the apex of the heart, avoiding damage to the conduction system in the interventricular septum and the atrioventricular valves 7 .…”
mentioning
confidence: 99%